PELAYANAN APARATUR DALAM PEMBERIAN IZIN MENDIRIKAN BANGUNAN (IMB) DI DINAS PENANAMAN MODAL DAN PERIZINAN TERPADU SATU PINTU KOTA JAYAPURA - Anugrah Yulistiono Ririhena; Irfan Setiawan (Institut Pemerintahan Dalam Negeri, 2018)
This study aims to analyze the Building Permit Letter Service in the apparatus service of the One Stop Office and One Stop Office in Jayapura and describe the obstacles in the process of granting Building Permit Letter. The research method used is qualitative research with descriptive method with inductive approach to present data about the apparatus service in the process of Building Permit Letter. The result of the research explains that the service of apparatus in providing building permit service letter at the Investment and One Stop Integrated License Department in Jayapura City of Papua Province has been running well and in accordance with Standard Operating Procedure of issuing Building Permit Letter, despite having some constraints such as; lack of network access, low public awareness, lack of facilities and infrastructure in the service of building permit letter. Keyword: building permit letter, apparatus, public service